Postcards from the Chihuahua Border : Revisiting a Pictorial Past, 1900s-1950s - Arreola, Daniel D. (Daniel David), 1950- (Book collections on Project MUSE., 2019)
"This book is a colorful and dynamic visual history of Mexico's northern border that draws on more than three decades of archival work and tells the history of border towns through picture postcards"--